Who Owns the Pilgrim Fathers? American Protestants and a Contested Legacy. Issue 3 (3rd July 2021) - Bendroth, Margaret
Abstract : This article charts a century of competition among American Protestants over the Pilgrims' legacy. The tug-of-war began in the 1820s, pitting Congregationalists against Unitarians, and grew to include other denominations with fewer reasons to celebrate the original Plymouth settlers, from Episcopalians and Baptists to Quakers and the AME Zion. It culminated in 1920, when ecumenists upheld a band of dissenting separatists as the true architects of Christian unity. This article argues that all of the back-and-forth helped to create American Protestant denominationalism, fine-tuning a competitive and often unwieldy system and providing a regular practice in the human intricacies of religious pluralism.